S73 The inflammatory response of airway epithelial cells to soluble mediators obtained from H. influenzae infected macrophages. (11th November 2022) - Carson, S; Lundy, FT; McGarvey, LP; Crilly, A; Martin, SL
Abstract : Introduction and Objectives: Acute exacerbations of chronic obstructive pulmonary disease (AECOPD) are often associated with infections from respiratory pathogens including Haemophilus influenzae . There is however, an incomplete understanding of the inflammatory response which involves complex interactions between pathogens, airway epithelial cells and immune cells. The aim of this study was to investigate the effect of pathogen-associated immune cell stimulus on airway epithelial cell responses. Methods: Differentiated THP-1 cells (a macrophage-like cell line) were infected with H. influenzae. The sterile-filtered THP-1 cell-conditioned media (TCCM), containing soluble mediators, was used to treat airway epithelial cells including the cell line 16HBE14o- (HBE) and primary bronchial epithelial cells (PBEC) from 2 healthy and 2 COPD donors. Changes in inflammatory mediators produced by airway epithelial cells were screened using a Proteome Profiler Human Cytokine Antibody Array and key targets validated by qPCR and ELISA. Results: TCCM treatment of HBE cells led to a significant increase in IL-8 levels (p<0.01) which was higher than that observed after direct H. influenzae infection of HBE cells. The Proteome Profiler screen identified changes in the levels of 13 inflammatory mediators in the cell-conditioned media of PBEC following TCCM treatment with 4 results of interest detailed in figure 1 . TCCM stimulated levels of IL-8, GM-CSF and G-CSF in PBEC from all donors, although for the latter a more blunted response was observed with the COPD donors compared to the healthy PBEC; relatively lower levels of gene expression were also determined by qPCR. SERPIN E1, also known as plasminogen activator inhibitor-1, was present at a higher level in PBEC cell-conditioned media from all donors compared to the TCCM however, upon treatment of the PBEC with TCCM, SERPIN E1 levels were reduced by over 50% in all cases, which was also confirmed by qPCR. Conclusions: The results of this study showed TCCM stimulation led to increased IL-8 levels from HBE cells above the levels seen from direct immunopathogenic stimulation of HBE cells. TCCM stimulated pro-inflammatory mediator production and expression within PBEC from healthy and COPD donors with G-CSF and SERPIN E1 identified as targets of interest for future work. Please refer to page A211 for declarations of interest related to this abstract.